The relationship between sirtuin 1 (SIRT1) expression and tumor size, Proliferating Cell Nuclear Antigen (PCNA) expression and histological grading in rat breast carcinoma induced by dimethylbenz(ï¡)anthracene (DMBA) - Harjadi, Irianiwati, Sitarina Widyarini, Novrita Padauleng Dewajani Purnomosari, Sri Herwiyanti (Universitas Gadjah Mada, 2013)
Controversy regarding the role of SIRT1 in pathology of cancers exists and is still under debate.SIRT1 could act as either a tumor supressor or tumor promotor. This study was conducted toevaluate the relationship between SIRT1 expression and tumor size, Proliferating Cell NuclearAntigen (PCNA) expression and histological grading in rat breast carcinoma induced bydimethylbenz(Ã¡)anthracene (DMBA). Thirty female Sprague Dawley rats were randomly allocatedinto three groups with 10 rats in each group. Group 1 as negative control was just fed thestandard food. Group 2 as vehicle control was fed the standard food and corn oil. Group 3 asinduction group was fed the standard food and induced with DMBA at dose of 20 mg/kg bodyweight (BW) in corn oil twice a week for five weeks. All rats were palpated weekly to determinethe appearance, size and location of tumors. Sixteen weeks after DMBA induction rats weresacrified and histological preparations of the breast carcinoma tissue were then processed forSIRT1 and PCNA expression examination as well as histological grading. The result showed thatSIRT1 expression was significantly higher in breast carcinoma tissue compared to normal gland(26.12 vs 0.05; p = 0.004). SIRT1-positive was observed mostly in poor histological gradecarcinomas (56.2%), and it was not observed in good histological grade carcinomas. However,there was no significantly difference between SIRT1 and histological grading (p = 0.097; r =0.285). A significant correlation between SIRT1 expression and the tumor size (p =0.009; r=0.877), as well as PCNA expression (p =0.000; r =0.790) was observed. In conclusion, thereis relationship between SIRT1 expression and tumor size as well as PCNA expression in rat breastcarcinoma induced by DMBA.